The Acceptance of Institute of Islamic Training Malaysia’s (ILIM) Staffs on The Leadership Practice Domain - Samah, Nor Shaidayani binti; Don, Abdul Ghafar bin; Mokhtar, Ahmad Irdha bin (International Journal of Membrane Science and Technology, 2023)
The development and progress of an organization are determined, among other by leadership factor. Literature suggests that leadership practices are crucial elements in influencing organizational management and performance. There are three domains emphasized in the discourse of leadership namely: Influencing people, two-ways interaction, and collaboration among organizational members. This article aims to examine the acceptance of these three domains in the leadership practices among staffs of the Institute of Islamic Training Malaysia (ILIM). The study employs a quantitative method through a questionnaire distributed to respondents via the Google Form application. The study sample involves 85 ILIM staff members from various levels, including management and professionals or support staff, located in Selangor. They have responded to questions related to leadership practices, encompassing influencing practices, interaction, and collaboration among members in effectively administering training program management. The responses provided indicate a significant correlation among the studied variables. This can be observed in the results of the Pearson correlation analysis related to leadership domains, which indicate that influencing skill elements and interaction skill elements are at r=.64, while the correlation between influencing skills and collaboration elements is at r=.46. Furthermore, the correlation between interaction skill elements and influencing elements is at r=.64, and the correlation between interaction elements and collaboration elements is at r=.56. Collaboration elements with influencing elements are at r=.46 and collaboration elements with interaction elements are at r=.56. The study reveals that the relationship between leadership practices and these elements shows a significant positive correlation, and ILIM staff members have the spirit and potential to become capable leaders in implementing effective training management administration. With this spirit, ILIM has successfully demonstrated its role as an authoritative Islamic training institution in providing effective services to enhance knowledge, skills, and efficient career ethics for all civil servants in Malaysia.